Preliminary effects of a red ginger–honey drink on symptoms of acute respiratory infection in toddlers: A quasi-experimental study - Ferri Arya Ardiyanto; Setiawati Setiawati; Linawati Novikasari (School of Health Sciences Al-Ma'arif, 2026)
Background: Acute respiratory infection (ARI) is a common cause of illness in children younger than five years. Red ginger and honey have anti-inflammatory, antimicrobial, antioxidant, and demulcent properties that may relieve respiratory symptoms, although pediatric evidence remains limited. Objective: To evaluate changes in body temperature, respiratory rate, cough frequency, and peripheral oxygen saturation among toddlers receiving usual care with or without an adjunctive red ginger–honey drink. Methods: A quasi-experimental nonequivalent pretest–posttest control-group study was conducted at the Labuhan Ratu Community Health Center, Bandar Lampung, in 2026. Thirty toddlers with physician-diagnosed ARI were selected purposively and allocated to an intervention group (n = 15) or a control group (n = 15). Both groups continued physician-prescribed care; the intervention group additionally received a drink prepared from 5–10 g of fresh red ginger in 150–200 mL of water plus 10 g of honey twice daily for five days. Paired-samples t tests and Wilcoxon signed-rank tests evaluated within-group changes. Results: Body temperature did not change significantly in either group (intervention p = .913; control p = .275). Respiratory rate decreased in both groups (both p = .001), cough frequency decreased in both groups (both p < .001), and oxygen saturation increased in both groups (intervention p = .002; control p = .013). The reduction in cough frequency was descriptively greater in the intervention group (mean change 8.267) than in the control group (mean change 7.200). Conclusion: Clinical improvement occurred in both groups. The red ginger–honey drink may have adjunctive potential, particularly for cough relief, but superiority over usual care cannot be established from within-group tests alone. Larger studies using randomized allocation, baseline comparability assessment, and direct between-group analyses are required.